(3aJGhi GdoSaOis - (3YWGA Gddg Hf MeRI GdSaOj GdSeQbfOj, CHh GdMSfs
(3ChdgG (B:s
(3jHOC HcJGH GdWgGQg s
(3BNQgG (B:s
(3jfJgi HcJGH GdhUGjG s
(3GdfSNI HgG MhGTs
(3HChdg agQSJs
(3GdJhKjbGJ GdeQLYjI (B:s
(3cTa GdXfhf dMGLi NdjaI(B: (3L (B2 - (3U (B1225s
(3eUOQ GbJfGA GdCUd (B:s
(3OGQ GdcJH GdeUQjI (B((3abg Mfai (B88) s
Keywords: (3Gdabg GdMfajs